2012
DOI: 10.1111/j.1538-7836.2011.04557.x
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution‐associated procoagulant changes: the role of circulating microvesicles

Abstract: Summary.  Background: Epidemiological studies suggest an association between exposure to particulate matter (PM) in air pollution and the risk of venous thromboembolism (VTE). Objectives: To investigate the underlying pathophysiological pathways linking PM exposure and VTE. Patients and methods: We assessed potential associations between PM exposure and coagulation and inflammation parameters, including circulating microvesicles, in a group of 233 patients with diabetes. Results: The numbers of circulating blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 50 publications
4
57
1
1
Order By: Relevance
“…The flow cytometry instrument settings and MP gating were adopted from previous works [2,12,16]. We used Megamix beads (BioCytex, Marseille, France) to determine the gate for MPs, as described previously [2,18]. Briefly, 0.5 μm, 0.9 μm and 3 μm beads were detected on an SSC/FL2 plot (Supplementary Fig.…”
Section: Flow Cytometric Analysis Of Pfp Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow cytometry instrument settings and MP gating were adopted from previous works [2,12,16]. We used Megamix beads (BioCytex, Marseille, France) to determine the gate for MPs, as described previously [2,18]. Briefly, 0.5 μm, 0.9 μm and 3 μm beads were detected on an SSC/FL2 plot (Supplementary Fig.…”
Section: Flow Cytometric Analysis Of Pfp Samplesmentioning
confidence: 99%
“…2B). MP gate was set on the FSC/SSC plot as described previously [2,12,18] ( Supplementary Fig. 2B and C).…”
mentioning
confidence: 99%
“…CS as well as PM exposure increases the release of phosphatidylserine (PS) + EV from different cell types in vitro and the concentrations of circulating PS + EV in vivo (Emmerechts et al 2012b;Li et al 2010;Neri et al 2016;Serban et al 2016). PS + EV may contribute to inflammation, as Serban et al (2016) reported that CSE-induced PS + EV from endothelial cells prevent efferocytosis of apoptotic cells by PS-dependent blocking of the phagocyte receptors for apoptotic cell engulfment.…”
Section: Interference With Efferocytosismentioning
confidence: 99%
“…Indeed prolonged exposure to air pollutans increases both the number of procoagulant vescicles and their procoagulant properties (Emmerechts J et al, 2012).…”
Section: Pathophysiological Mechanism Linking Particulate Matter (Pm)mentioning
confidence: 99%